Aggressive Attitudes in Middle Schools: A Factor Structure and Criterion-Related Validity Study. (August 2015) - Huang, Francis L.; Cornell, Dewey G.; Konold, Timothy R.
Student attitudes toward aggression have been linked to individual aggressive behavior, but the relationship between school-wide normative beliefs about aggression and aggressive behavior poses some important measurement challenges that have not been adequately examined. The current study investigated the factor structure, measurement invariance, and criterion-related validity of a six-item Aggressive Attitudes scale using a large sample of seventh- and eighth-grade students ( n = 39, 364) from 423 schools. Analytic procedures accounted for the frequently ignored modeling problems of clustered and ordinal data to provide more reliable and accurate model estimates and standard errors. The resulting second-order factor structure of the Aggressive Attitudes scale demonstrated measurement invariance across gender, grade, and race/ethnicity groups. Criterion-related validity was supported with eight student- and school-level indices of aggressive behavior.